Compondo uma constelação no protagonismo da comunidade escolar para a construção do projeto político-pedagógico emancipatório - Tedesco, Sirlei (My University, 2022)
This research, entitled "Composing a constellation in the protagonism of the school community for the construction of the emancipatory Political-Pedagogical Project", starts from the following question-problem: How to build the Political-Pedagogical Project, based on emancipatory horizons, articulated to the protagonism of the school community in Fagundes Varela? The objective is, from the analysis of the contributions of the construction process of the Political-Pedagogical Project in the municipal school system of Fagundes Varela, revealing ruptures and/or resistance, to build guidelines for a new Political-Pedagogical Project. The approach used for this study follows the perspective of action research, developed with the participation of the school community of an institution of Kindergarten and Early Years of Elementary School, located in the municipality of Fagundes Varela, in the interior of Rio Grande do Sul. Theoretical foundations come from the Critical Theory of Society, notably from authors who were part of the first generation of the Frankfurt School - Theodor Adorno and Walter Benjamin - in constant dialogue with other authors, theories, and the researcher's personal experiences. The path of data collection, treatment, and analysis from a qualitative conception, with the support of quantitative data, triangulates with the theoretical repertoire of Paulo Freire, René Barbier, Maurice Halbwachs, Rodolfo Kusch, Wolfgang Leo Maar, Bruno Pucci, Márcio Seligmann-Silva, and Ilma Passos Alencastro Veiga, designed by the sample of 50% of teachers, 10% of family nuclei, and 11.6% of students from public schools, the locus of the research, through discursive textual analysis. The results analyzed through the description of the process of construction of the Political-Pedagogical Project of the School advocated the process of involving the school community, its conceptions, reflections and (re)significations, from statements/announced, validated and delivered to the Caminhos School Community Learning, which advocate: change management skills; world and local context readings; conceiving cooperation as a virtue for the "materialization" of the Unprecedented Viable; transcending the vertical hierarchical; create contexts that unleash creativity; reflect on the experience of having lived through the COVID 19 Pandemic in a response to the world based on full citizenship; incorporate the Political-Pedagogical Project as a living ecosystem; presupposing daily praxis from living and not ready responses; leaving the culture of fragmentation for a culture of reception and, finally, the delivery of a Pedagogical Documentation of and for the community validated by the group and in a continuous process of construction and renewed validation. The relevance of the work consists of the intention to broaden visions and open paths to new questions, doubts and research, inspiring, even, other realities to develop the construction of their emancipatory Political-Pedagogical Projects, with the collaboration and protagonism of the school community. [resumo fornecido pelo autor]
Esta pesquisa, intitulada "Compondo uma constelação no protagonismo da comunidade escolar para a construção do Projeto Político-Pedagógico emancipatório", parte da seguinte questão-problema: Como construir o Projeto Político-Pedagógico, embasado em horizontes emancipatórios, articulado ao protagonismo da comunidade escolar, em escola de ensino municipal de Fagundes Varela? O objetivo é, a partir da análise das contribuições do processo de construção do Projeto Político-Pedagógico na rede municipal de ensino de Fagundes Varela, reveladora de rupturas e/ou resistências, construir diretrizes para um novo Projeto Político-Pedagógico. A abordagem utilizada para este estudo segue a perspectiva da pesquisa-ação, desenvolvida com a participação da comunidade escolar de uma instituição de Educação Infantil e Anos Iniciais do Ensino Fundamental, localizada no município de Fagundes Varela, no interior do Rio Grande do Sul. As bases teóricas são provenientes da Teoria Crítica da sociedade, notadamente de autores que fizeram parte da primeira geração da Escola de Frankfurt - Theodor Adorno e Walter Benjamin -, em constante diálogo com Paulo Freire e outros teóricos, além de fragmentos literários provenientes das obras de Manuel de Barros e José Saramago, teorias e experiências pessoais da pesquisadora. O percurso de geração, tratamento e análise dos dados emergentes de uma concepção qualitativa, com o suporte de dados quantitativos, triangulam com o repertório teórico de René Barbier, Maurice Halbwachs, Rodolfo Kusch, Wolfgang Leo Maar, Bruno Pucci, Márcio Seligmann-Silva e Ilma Passos Alencastro Veiga, por meio da análise textual discursiva. Os resultados analisados mediante a descrição do processo de construção do Projeto Político-Pedagógico da Escola preconizaram o processo de envolvimento da comunidade escolar, suas concepções, reflexões e (re)significações, a partir de enunciados/anunciados, validados e entregues à Comunidade Escolar Caminhos do Aprender, os quais preconizam: competências de gestão de mudanças; leituras de mundo e de contexto local; conceber a cooperação como virtude para a "materialização" do Inédito Viável; transcender do hierárquico vertical; criar contextos que libertam a criatividade; refletir acerca da experiência de ter vivenciado a Pandemia COVID 19 em uma resposta ao mundo com base na cidadania plena; incorporar o Projeto Político-Pedagógico como um ecossistema vivo; pressupor as práxis cotidianas a partir de respostas vivas e não prontas; sair da cultura de fragmentação para uma cultura de acolhimento e por fim, a entrega de uma Documentação Pedagógica da e para a comunidade validada pelo grupo e em contínuo processo de construção e de renovada validação. A relevância do trabalho consiste na intenção de ampliar visões e abrir caminhos para novas perguntas, dúvidas e pesquisa, inspirando, inclusive, outras realidades a desenvolver a construção de seus Projetos Político- Pedagógicos emancipatórios, com a colaboração e o protagonismo da comunidade escolar. [resumo fornecido pelo autor]
Keywords: Educação - Finalidades e objetivos - Fagundes Varela (RS); Planejamento educacional - Fagundes Varela (RS); Escolas municipais - Fagundes Varela (RS); Comunidade e escola; Democratização da educação; Education - Aims and objectives - Fagundes Varela (Brazil); Educational planning - Fagundes Varela (Brazil); Municipal Schools - Fagundes Varela (Brazil); Community and school